2006
DOI: 10.1128/iai.74.5.2917-2924.2006
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine mRNA Expression inMycobacteriam ulcerans-Infected Human Skin and Correlation with Local Inflammatory Response

Abstract: Cytokine mRNA expression in biopsies of Mycobacterium ulcerans-infected human tissue was investigated using real-time PCR, and the findings were correlated with the clinical stages of disease and histopathologies. A broad range of cytokine mRNAs were detected in 16 early nodules and 28 late-stage ulcers, including those for the Th1 cytokines tumor necrosis factor alpha (TNF-␣) and gamma interferon (IFN-␥) and the Th2 cytokine interleukin 10 (IL-10). IFN-␥ was strongly expressed in both nodules and ulcers, sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
26
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 38 publications
3
26
0
Order By: Relevance
“…Our findings are in line with several studies with human BU patients suggesting that IFN-g is associated with protection (24,27,39,49). This cytokine was firstly suggested to play a role in the control of M. ulcerans infections by Gooding et al (24,39), who report that PBMCs from patients with past BU, but not from healthy contacts, display low capacity to produce IFN-g after stimulation with live M. ulcerans or Mycobacterium bovis bacillus Calmette-Guérin (BCG).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Our findings are in line with several studies with human BU patients suggesting that IFN-g is associated with protection (24,27,39,49). This cytokine was firstly suggested to play a role in the control of M. ulcerans infections by Gooding et al (24,39), who report that PBMCs from patients with past BU, but not from healthy contacts, display low capacity to produce IFN-g after stimulation with live M. ulcerans or Mycobacterium bovis bacillus Calmette-Guérin (BCG).…”
Section: Discussionsupporting
confidence: 78%
“…These results show that, as in human BU lesions (24,25,27), IFN-g is expressed in the infection foci of mice infected with M. ulcerans. Next, we decided to investigate the biological activity of this cytokine in experimental infections by comparing the proliferation of the different M. ulcerans strains in footpads of IFNg-deficient mice or wild-type (WT) counterparts.…”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…It has been recently shown that M. ulcerans has an intramacrophage growth phase (84), which is in accordance with the occurrence of cell-mediated immunity and delayed-type hypersensitivity responses in BU patients (20,35,36,40,41,49,53,54,58,64,66,76,78,82,86,87). The correlation between the amounts of TNF produced by macrophages infected with different strains of M. ulcerans and the mycolactones produced by these strains, as well as the biological relevance of TNF in the progression of infection by M. ulcerans, is currently unknown.…”
mentioning
confidence: 77%